Proceedings of the 36th Annual ACM Symposium on Applied Computing 2021
DOI: 10.1145/3412841.3441930
|View full text |Cite
|
Sign up to set email alerts
|

Energy-aware scheduling of multi-version tasks on heterogeneous real-time systems

Abstract: The emergence of battery-powered devices has led to an increase of interest in the energy consumption of computing devices. For embedded systems, dispatching the workload on different computing units enables the optimisation of the overall energy consumption on high-performance heterogeneous platforms. However, to use the full power of heterogeneity, architecture specific binary blocks are required, each with different energy/time trade-offs. Finding a scheduling strategy that minimises the energy consumption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…The energy aware scheduling of dependent AC tasks were considered in some prior works [36], [37] that employed DVFS at the cores. Most of the prior energy/thermal management mechanisms [14], [17], [28] control the dynamic power of the cores in CMPs either by employing DVFS [41], [42] or by migrating tasks [13], [19], [20]. Recently, Roeder et al [42] showed the effectiveness of DVFS, planned offline, for a heterogeneous real-time system with multi-version based taskmodel, but energy efficiency can be enhanced dynamically based on the runtime tasks' as well as system's characteristics.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy aware scheduling of dependent AC tasks were considered in some prior works [36], [37] that employed DVFS at the cores. Most of the prior energy/thermal management mechanisms [14], [17], [28] control the dynamic power of the cores in CMPs either by employing DVFS [41], [42] or by migrating tasks [13], [19], [20]. Recently, Roeder et al [42] showed the effectiveness of DVFS, planned offline, for a heterogeneous real-time system with multi-version based taskmodel, but energy efficiency can be enhanced dynamically based on the runtime tasks' as well as system's characteristics.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Most of the prior energy/thermal management mechanisms [14], [17], [28] control the dynamic power of the cores in CMPs either by employing DVFS [41], [42] or by migrating tasks [13], [19], [20]. Recently, Roeder et al [42] showed the effectiveness of DVFS, planned offline, for a heterogeneous real-time system with multi-version based taskmodel, but energy efficiency can be enhanced dynamically based on the runtime tasks' as well as system's characteristics. Donald and Martonosi [14] have shown the efficacy of different DVFS techniques along with task migration policies to control temperature, where distributed DVFS applied with task migration are claimed to be the best.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Approaches exist without applying a fault tolerance policy, e.g., the task mapping problem is decomposed into a sub-problem that satisfies the reliability constraint and another that minimizes resources [5] and a whale optimization algorithm is proposed [6]. In [7], the scheduling algorithm for dependent multi-version tasks is studied based on Forward List Scheduling with the goal of minimizing the total energy consumption under real-time constraint. Approaches execute a recovery task, e.g., individual [8] or shared [2,9], or both [10], with maximum frequency, exploring available time slack to meet the reliability constraint.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…Roeder et al,. [20] have experimented to reduce total energy usage, this paper provides an off-line scheduling approach based on forward list scheduling for dependent multi version tasks. Our heuristic allows apps to dynamically adjust voltage and frequency while they were running since it takes into consideration Dynamic Voltage and Frequency Scaling (DVFS).…”
Section: Literature Reviewmentioning
confidence: 99%